Awareness and implementation of green practices : a case study of MICE operators in Phuket, Thailand - Garin, Florence Anjali (Prince of Songkla University, 2019)
Thesis ((M.B.A., Hospitality and Tourism Management (International program))--Prince of Songkla University, 2018